2006
DOI: 10.1258/135763306778558178
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the methodology of telemedicine evaluation in patients with postural and movement disorders

Abstract: We reviewed the methodology used in telemedicine research concerning patients with postural and movement disorders. Literature searches were performed using various computerized databases through to October 2005. Twenty-two studies met the criteria for review. Two broad models of telemedicine delivery were represented in the literature: (1) telemedicine between health-care professionals at each telemedicine site (n=16) and (2) telemedicine between health-care professionals and a patient at a remote site (n=6).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Further benefits include increased care delivery, increased professional education, provision of care not previously delivered, quality control in screening programmes and reduced health-care costs. 12,13…”
Section: Introductionmentioning
confidence: 99%
“…Further benefits include increased care delivery, increased professional education, provision of care not previously delivered, quality control in screening programmes and reduced health-care costs. 12,13…”
Section: Introductionmentioning
confidence: 99%
“…Reviews of TR have reported that there is promise in this area, but have drawn attention to the limitations of available evidence. Huis et al 3 reported that evaluation of the effects of some categories of TR interventions is still in its early stages, with an emphasis on technical feasibility and acceptability. Such limitations were also considered by Russell who noted that much research in telemedicine for physical rehabilitation has been technology-focused, and with small sample research designs.…”
Section: Introductionmentioning
confidence: 99%
“…The search identified 55 systematic reviews. 155 The details of their selection are summarised in Table 1. The categories in which most reviews had been conducted were home telecare (16) and general (16), which together accounted for over half of the published papers which were selected for the present study (see Table 2).…”
Section: Resultsmentioning
confidence: 99%